Construction of 2-alkynyl aza-spiro[4, 5]indole scaffolds via sequential C–H activations for modular click chemistry libraries. Issue 69 (10th August 2021) - Zhang, Jun; Wang, Mengmeng; Wang, Huiying; Xu, Hui; Chen, Junjie; Guo, Ziqiong; Ma, Biao; Ban, Shu-Rong; Dai, Hui-Xiong
Abstract : Herein, we have developed a strategy of sequential C–H activations of indole to construct novel 2-alkynyl aza-spiro[4, 5]indole scaffolds, which incorporated both alkyne and spiro-units into indole. Abstract : Herein, we have developed a strategy of sequential C–H activations of indole to construct novel 2-alkynyl aza-spiro[4, 5]indole scaffolds, which incorporated both alkyne and spiro-units into indole. Gram-scale synthesis and a one-pot, three-step synthesis demonstrated the utility of this protocol. Hybrid conjugates with an oseltamivir derivative further offered a powerful tool for the construction of a versatile spiroindole-containing library via click chemistry.